2011
DOI: 10.1258/la.2010.010102
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of warm ischaemia predamaged porcine kidneys by fibrinolytic preflush with streptokinase: reduction of animal experiments

Abstract: In order to reduce the number of animal experiments, the use of non-heart-beating donors (NHBDs) from a commercial abattoir has been proposed. Since the use of slaughterhouse organs is legally not defined as animal experiment, this would fulfil international standards as an alternative to animal experiments. The development of intravascular thrombosis after cardiac arrest negatively impacts organ preservation and thus viability during ischaemic storage and reperfusion. A fibrinolytic preflush with streptokinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Szyrach et al [26] reported on flow-controlled normothermic reperfusion of porcine kidneys after cold storage in HTK for 3 h using the same flow rate (1 ml/min/g), resulting in a MAP which did not exceed 110 mm Hg. In our study, the longer but clinically more relevant cold ischemic period of 24 h could account for the increase in MAP, ultimately reaching more than 200 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Szyrach et al [26] reported on flow-controlled normothermic reperfusion of porcine kidneys after cold storage in HTK for 3 h using the same flow rate (1 ml/min/g), resulting in a MAP which did not exceed 110 mm Hg. In our study, the longer but clinically more relevant cold ischemic period of 24 h could account for the increase in MAP, ultimately reaching more than 200 mm Hg.…”
Section: Discussionmentioning
confidence: 99%